Identification of bread wheat genotypes (Triticum aestivum L.) with tolerance to drought conditions at the central coast of Peru - Gomez-Pando, L. (2022)
Wheat is sown mostly in Peru, in areas above 3000 m altitude, under rainfed conditions and frequent drought problems during the crop cycle. It is a cereal used as a staple food by the families of small-scale farmers who are dedicated to their cultivation, which is why it is necessary to develop varieties with drought tolerance. This investigation had as objectives (1) to determine the yield potential of wheat genotypes under drought stress conditions, (2) to determine the susceptibility indices and drought tolerance, and (3) to identify drought tolerant genotypes. Nine genotypes introduced from CIMMYT and the commercial variety “Centenario” wheat flour (Triticum aestivum L.) were studied in an environment with complete irrigation during the life cycle and another environment with terminal drought stress or deficit irrigation applied in the boot phase (Z4.0). A Random Complete Blocks design was used with three repetitions. Agronomic characteristics, quality evaluations were carried out following the established protocols for each characteristic evaluated and the stress tolerance indices (STI), mean productivity (MP), geometric mean productivity (GMP), tolerance index (TOL), and stress susceptibility index (SSI), were determined. The reduction in the grain yield varied from 17.95 % to 33.27 % mainly due to drought. The SSI ranged from 0.65 (G-3) to 1.21 (G-6 y G-9), meanwhile the TOL ranged from 1 316.8 (G-3) to 3 142.68 (G-7). The MP, STI and GMP indexes allowed the identification of genotypes with the greatest tolerance to irrigation and stress conditions of the 5 genotypes: G- 1, G-2, G-7, G-8 and G- 10. These results are important for developing new varieties that adapt to drought conditions and to face climate change in the Andean region.